Textual Authority and Historical Interpretation: Revisiting Classical Sources Through Critical Philology - Fahrizal Fahrizal; Andres Villanueva; Catherine Li (Journal of Humanities Research Sustainability, 2026)
Background. Classical texts have long served as the foundation for historical interpretation, shaping our understanding of past events, philosophies, and cultural legacies. However, the authority of these texts has been questioned as critical philology increasingly reveals the complex layers of translation, adaptation, and contextualization that shape historical narratives. Revisiting classical sources through the lens of critical philology allows for a more nuanced understanding of their role in historical interpretation and the authority they hold in shaping intellectual and cultural traditions. Purpose. This study aims to examine the authority of classical texts in historical interpretation, focusing on how critical philology can reveal the ways in which these texts have been manipulated, adapted, and re-contextualized. It explores the implications of these processes for our understanding of historical events and intellectual traditions. Method. A critical philological approach is employed, analyzing key classical texts alongside their translations, commentaries, and later adaptations. Textual analysis is complemented by historical contextualization to uncover the shifts in meaning and authority across different periods and cultures. Results. The study reveals that classical texts are not fixed repositories of knowledge but dynamic works whose meanings have evolved over time. The manipulation of these texts in different historical contexts significantly affects their authority in shaping historical narratives. Conclusion. This research demonstrates the importance of revisiting classical sources through critical philology to reassess their role in historical interpretation, offering new insights into the fluid nature of textual authority.